Critical Thinking, Literacy, and Numeracy as Factors in STEM: Madrasah Student Learning (Program Studi Pendidikan Agama Islam, 2024)
In the era of massive information sources, the ability of the young generation to have critical thinking, literacy, and numeracy skills is needed. These three variables are the focus of this study: how are students' abilities in critical thinking, literacy, and numeracy using STEM-based learning? To answer this problem, the researchers employed mixed research with an explanatory sequential design. The researchers used quantitative analysis and then utilized qualitative. The findings of this study revealed that STEM exerted a good influence on student learning. The findings of this study also stated that the ability of students to think critically was in a good category (n=76,55), literacy was in a good category (n=3,58), and numeracy was in a neutral category (n=58,57). In addition, the researchers uncovered that STEM is an alternative to teaching science and produces critical thinking, literacy, and numeracy skills.